Joint Europa Mission (JEM): a multi-scale study of Europa to characterize its habitability and search for extant life. (15th November 2020) - Blanc, Michel; Prieto-Ballesteros, Olga; André, Nicolas; Gomez-Elvira, Javier; Jones, Geraint; Sterken, Veerle; Desprats, William; Gurvits, Leonid I.; Khurana, Krishan; Balmino, Georges; Blöcker, Aljona; Broquet, Renaud; et al.
Abstract: Europa is the closest and probably the most promising target to search for extant life in the Solar System, based on complementary evidence that it may fulfil the key criteria for habitability: the Galileo discovery of a sub-surface ocean; the many indications that the ice shell is active and may be partly permeable to transfer of chemical species, biomolecules and elementary forms of life; the identification of candidate thermal and chemical energy sources necessary to drive a metabolic activity near the ocean floor. In this article we are proposing that ESA collaborates with NASA to design and fly jointly an ambitious and exciting planetary mission, which we call the Joint Europa Mission (JEM), to reach two objectives: perform a full characterization of Europa's habitability with the capabilities of a Europa orbiter, and search for bio-signatures in the environment of Europa (surface, subsurface and exosphere) by the combination of an orbiter and a lander. JEM can build on the advanced understanding of this system which the missions preceding JEM will provide: Juno, JUICE and Europa Clipper, and on the Europa lander concept currently designed by NASA (Maize, report to OPAG, 2019). We propose the following overarching goals for our Joint Europa Mission (JEM): Understand Europa as a complex system responding to Jupiter system forcing, characterize the habitability of its potential biosphere, and search for life at its surface and in its sub-surface and exosphere. We address these goals by a combination of five Priority Scientific Objectives, each with focused measurement objectives providing detailed constraints on the science payloads and on the platforms used by the mission. The JEM observation strategy will combine three types of scientific measurement sequences: measurements on a high-latitude, low-altitude Europan orbit; in-situ measurements to be performed at the surface, using a soft lander; and measurements during the final descent to Europa's surface. The implementation of these three observation sequences will rest on the combination of two science platforms: a soft lander to perform all scientific measurements at the surface and sub-surface at a selected landing site, and an orbiter to perform the orbital survey and descent sequences. We describe a science payload for the lander and orbiter that will meet our science objectives. We propose an innovative distribution of roles for NASA and ESA; while NASA would provide an SLS launcher, the lander stack and most of the mission operations, ESA would provide the carrier-orbiter-relay platform and a stand-alone astrobiology module for the characterization of life at Europa's surface: the Astrobiology Wet Laboratory (AWL). Following this approach, JEM will be a major exciting joint venture to the outer Solar System of NASA and ESA, working together toward one of the most exciting scientific endeavours of the 21st century: to search for life beyond our own planet. Highlights: In this article we are proposing that ESA collaborates with NASA to design and fly jointly an ambitious planetary mission: the Joint Europa Mission (JEM). The JEM observation strategy will combine three types of scientific measurement sequences. The implementation of these three observation sequences will rest on the combination of two science platforms. We describe a science payload for the lander and orbiter that will meet our science objectives. We propose an innovative distribution of roles for NASA and ESA.